Did the Maids Return? The Long History of Devaluing Care Work and the Mixed Economy of Welfare - Kramer, Nicole (Historein, 2024)
For several years now, sociologists studying paid domestic care work have been arguing that the servant culture of the nineteenth century has returned. They focus on specific forms of care work: that done as informal or illegal employment, mostly carried out by migrants. To an historian, such a reference to the past is most intriguing. This article looks at the servant of the past to shed new light on the emergence of an informal labour market for care work. After outlining the arguments of sociologists about “the return of the maids”, it looks back at the history of servants. What was their role regarding long-term care for older disabled people? Furthermore, it sketches the changes regarding professional care at home and, finally, sheds some light on the emergence of a shadow market where migrants offer their services. In doing so, families should be brought into focus as agents of care within the mixed economy of welfare.